EMPIRICAL STUDY OF DEFERRED TAX ASSETS AND CORPORATE GOVERNANCE ON FINANCIAL PERFORMANCE OF FOOD AND BEVERAGE SUB-SECTOR MANUFACTURING COMPANIES LISTED ON THE IDX IN 2019-2022 - Vivian Vivian; Ricky Bryan D. P. Tampubolon (SEAN Institute, 2023)
Financial performance is an important factor in assessing the company's success, generally measured by its earnings position. The objective of this study is to investigate the effect of deferred tax assets and corporate governance on the financial performance of companies. The sample consists of companies in the food and beverage manufacturing sub-sector listed on the Indonesia Stock Exchange for the period 2019-2022, using secondary data from annual reports. A purposive sampling of 16 companies was selected. IBM SPSS Statistics 25 software is used to generate the data sets. The results showed that deferred tax assets (X1) have no effect on financial performance with a result 0.521 > 0.05, independent board of commissioners (X2) has a positive effect on financial performance with a result 0.005 < 0.05, board of directors (X3) has positive effect on financial performance with a result 0.000 < 0.05, nomination and remuneration committee (X4) has no effect on financial performance with a result 0.235 > 0.05. Meanwhile, deferred tax assets, independent board of commissioners, board of directors, nomination and remuneration committee simultaneously affect financial performance with a result 0.000 < 0.05.